Corporate Governance And Sustainability In Italian Large-Scale Retail Companies - Riboldazzi, Sabina (European Scientific Journal, ESJ, 2016)
The growing complexity of today’s business systems due to the economic globalization has led to a substantial modification of current corporate governance principles and approaches. In particular, the application of good corporate governance principles has increasingly required a clear focus on sustainability, which minimizes risks and, at the same time, ensures a positive outlook for the future of the company itself. Through the analysis of corporate governance systems, this study deepens the link between corporate governance and sustainability in retail companies, with particular emphasis on the Italian grocery retail system. The study highlights that innovation and process efficiency, promoted and implemented by a governance that values fairness and transparency, allow retail companies to obtain consensus and resources, thereby triggering a virtuous circle of sustainable business development.